Peroxisome proliferator-activated receptor agonists modulate neuropathic pain: a link to chemokines? - Freitag, Caroline M.; Miller, Richard J. (Frontiers in Cellular Neuroscience, 2014)
Chronic pain presents a widespread and intractable medical problem. While numerous pharmaceuticals are used to treat chronic pain, drugs that are safe for extended use and highly effective at treating the most severe pain do not yet exist. Chronic pain resulting from nervous system injury (neuropathic pain) is common in conditions ranging from multiple sclerosis to HIV-1 infection to type II diabetes. Inflammation caused by neuropathy is believed to contribute to the generation and maintenance of neuropathic pain. Chemokines are key inflammatory mediators, several of which (MCP-1, RANTES, MIP-1α, fractalkine, SDF-1 among others) have been linked to chronic, neuropathic pain in both human conditions and animal models. The important roles chemokines play in inflammation and pain make them an attractive therapeutic target. Peroxisome proliferator-activated receptors are a family of nuclear receptors known for their roles in metabolism. Recent research has revealed that PPARs also play a role in inflammatory gene repression. PPAR agonists have wide-ranging effects including inhibition of chemokine expression and pain behavior reduction in animal models. Experimental evidence suggests a connection between PPAR agonists' pain ameliorating effects and suppression of inflammatory gene expression, including chemokines. In early clinical research, one PPARα agonist, palmitoylethanolamide, shows promise in relieving chronic pain. If this link can be better established, PPAR agonists may represent a new drug therapy for neuropathic pain.